PENERAPAN MODEL INKUIRI FORMAT DIVERGENT DALAM PEMBELAJARAN PENCAK SILAT DI SEKOLAH DASAR Penelitian Tindakan kelas pada siswa kelas V - Bayu Erlangga, - (2019)
The background of this research is the problem in fifth-grade students of SDN 044 Cicadas Awigombong Bandung that is a lack of enthusiastic students in the learning of Pencak Silat. The purpose of this research is to improve the basic learning outcomes in Pencak Silat learning through Inquiry models with Divergent format in Elementary Schools. This research was performed because of the many uses of a monotonous learning model in basic motion learning in the Pencak Silat, so the enthusiasm and participation of students in receiving the learning is still lacking. The research method used is the research Action Class (PTK) in 33 students in grade V SDN 044 Cicadas Awigombong Bandung City. The results of preliminary observations show the learning outcomes of students' basic silat moves are low, that is 31.00% in the cognitive aspect, 56.00% in the affective aspect, and 29.00% in the psychomotor aspect. Research in the cycle I of action 1 showed results, that is 40.45% in the cognitive aspect, 57.94% in the affective aspect, and 40.00% in the psychomotor aspect. The cycle I of action 2 showed the results of 51.30% in the cognitive aspect, 69.06% in the affective aspect, and 50.71% in the psychomotor aspect. In cycle II action 1 shows 60.55% in the cognitive aspect, 78.76% in the affective aspect, and 67.73% in the psychomotor aspect. In cycle II action 2 achieves 78.76% in the cognitive aspect, 86.82% in the affective aspect, and 83.08% in the psychomotor aspect. From the research data that has been done, it can be concluded that the implementation of inquiry models with divergent format on Pencak Silat learning, can improve the silat basic motion learning outcomes on the cognitive, affective, and psychomotor aspects. Key Words: Inquiry Models with Divergent Format, Learning Outcomes, Basic Motion, Pencak Silat.